(untitled) (International Journal of Biology and Chemistry, 2019)
miRNA regulates the expression of a large number of genes, including plant transcription factors. It is important to reveal miRNA associations with the corresponding targets in order to increase plant productivity and resistance to biotic and abiotic stresses. One of such targets is the group of MYB transcription factor genes, involved in the regulation of some of the most important physiological processes. The search for miRNA target genes was performed using the MirTarget program, which calculates the free energy (ΔG) of miRNA binding with mRNA; position and schemes of the potential binding sites. The relative amount of free energy (ΔG/ΔGm) was used as a comparative criterion for evaluating the degree of interaction of miRNA and mRNA. The binding sites for tae-miR1127b-3p, tae-miR159a,b-3p, tae-miR164-5p, tae-miR171a-3p, tae-miR319-3p, tae-miR397-3p, tae-miR444a,b-3p, tae-miR5084-3p, tae-miR531-5p, tae-miR5384-3p, tae-miR9652-5p, tae-miR9663-5p, tae-miR9666a-3p, tae-miR9676-5p, tae-miR9778-5p, tae-miR9779-3p, tae-miR9780-3p were found in mRNAs of 258 MYB family genes in Triticum (T.) aestivum. miRNAs orthologs of T. aestivum, Arabidopsis thaliana, Zea mays and Oryza sativa had binding sites in mRNAs of MYB family genes of these and other plant species. tae-miR159a,b-3p binding sites are located in the CDS and encode the WSSIRSK oligopeptide, conserved in the proteins of the MYB transcription factors of 22 plant species. Аmino acid sequences of the MYB family proteins containing ELPSNQ oligopeptide are encoded by tae-miR159a,b-3p binding sites located in the third open reading frame in the mRNAs of the other 20 plant species. For each miRNA, groups of target genes of transcription factors are established. The schemes of interaction of the nucleotide sequences of the studied miRNAs with the nucleotide sequences of the mRNA genes of the transcription factors of the MYB family were constructed. Considered associations of miRNAs and genes can be used as markers of control of plant physiological processes in plant growth selection and regulation.